Heart rate recovery after physical exertion tests in elderly hypertensive patients undergoing resistance training - Murillo Jales Lins de Lira; Ivan Daniel Bezerra Nogueira; Juliana Fernandes de Souza; Flávio Emanoel Souza de Melo; Ingrid Guerra Azevedo; Patrícia Angélica de Miranda Silva Nogueira
Abstract Introduction: Heart rate recovery after exercise is a valuable variable, associated with prognosis and it has been used as an indicator of cardiorespiratory fitness, especially in patients with heart disease, as hypertensive patients. Objective: This study aimed to analyze the response of heart rate recovery in elderly hypertensive patients undergoing a resistance training program. Methods: Sample was composed for 10 elderly women with a mean age of 70.7 ± 7.4 years. Exercise test and six-minute walk test were developed and we checked heart rate recovery in the 1st and 2nd minute post tests, before and after resistance training. Results: There was an increase in mean heart rate recovery in the analyzed minutes in both tests, but only in the 1st minute after six minutes walk test we found a significant increase (p = 0.02). Conclusion: The results suggest the efficacy of resistance training to improve cardiorespiratory fitness of elderly hypertensive patients.